2017
DOI: 10.1111/bjso.12217
|View full text |Cite
|
Sign up to set email alerts
|

Stress‐testing the affect misattribution procedure: Heterogeneous control of affect misattribution procedure effects under incentives

Abstract: The affect misattribution procedure (AMP) is widely used to measure sensitive attitudes towards classes of stimuli, by estimating the effect that affectively charged prime images have on subsequent judgements of neutral target images. We test its resistance to efforts to conceal one's attitudes, by replicating the standard AMP design while offering small incentives to conceal attitudes towards the prime images. We find that although the average AMP effect remains positive, it decreases significantly in magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…In light of the findings of Hazlett and Berinsky (2018), it is possible that the extreme manipulations of person impressions in the current work (with Bob/Francis portrayed as very strongly positive or negative at each point in time) might have created a heightened awareness in participants of the possibility of being biased by the primes, and perhaps increased their motivation to avoid such influence so as to properly complete the task. If the ability of participants to successfully avoid any influence of the primes when motivated to do so takes a bimodal distribution, with most people either very skilled or very unskilled, then their ultimate scores on the AMP would be bimodal as well.…”
Section: Future Directionsmentioning
confidence: 92%
See 2 more Smart Citations
“…In light of the findings of Hazlett and Berinsky (2018), it is possible that the extreme manipulations of person impressions in the current work (with Bob/Francis portrayed as very strongly positive or negative at each point in time) might have created a heightened awareness in participants of the possibility of being biased by the primes, and perhaps increased their motivation to avoid such influence so as to properly complete the task. If the ability of participants to successfully avoid any influence of the primes when motivated to do so takes a bimodal distribution, with most people either very skilled or very unskilled, then their ultimate scores on the AMP would be bimodal as well.…”
Section: Future Directionsmentioning
confidence: 92%
“…A recent investigation by Hazlett and Berinsky (2018) offers evidence of one potential source of bimodality on the AMP. Participants in that study were placed in one of several conditions that ranged in the degree to which participants were incentivized to avoid showing any influence of the primes on their responses on the AMP, and then completed an AMP that used universally pleasant or unpleasant stimuli as primes.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the AMP offers several advantages to existing measures used to approximate emotional experiences, the AMP may also face unique limitations. One concern that researchers have raised is whether responses on the AMP are driven controlled rather than automatic processes (Bar-Anan & Nosek, 2012; Hazlett & Berinsky, 2018; Teige-Mocigemba, Penzl, Becker, Henn, & Klauer, 2015). For example, researchers have found that sufficiently motivated participants may modify their responses on a way that reduces priming effects on the AMP (Hazlett & Berinsky, 2018; Teige-Mocigemba et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent “punishment phase,” participants could decide which player should receive a noise blast; its delivery was however determined by the computer, which allowed blasting of both players. Affective reactions after each noise punishment were measured with the affect misattribution procedure (AMP; Payne et al, 2005), which provides a composite measure of momentary affects that is fairly robust against strategic deliberations (Deutsch & Gawronski, 2009; Eder & Deutsch, 2015; Hazlett & Berinsky, 2018; for a review, see Payne & Lundberg, 2014). If sweet feelings dominate following revenge, AMP positivity scores should be larger following punishments of provoking compared to nonprovoking players.…”
Section: Methodsmentioning
confidence: 99%